A Nonword Repetition Task Discriminates Typically Developing Italian-German Bilingual Children From Bilingual Children With Developmental Language Disorder: The Role of Language-Specific and Language-Non-specific Nonwords - Eikerling, Maren Rebecca; Bloder, Theresa Sophie; Lorusso, Maria Luisa (Frontiers in Psychology, 2022)
In bi- and monolingual children, nonword repetition tasks (NWRTs) differentiate between typically developing (TD) and children with Developmental Language Disorder (DLD). Language specificity is a crucial factor in nonword construction especially for multilingual children. While language-specific nonwords seem less artificial than non-specific nonwords, the application of language-specific phonemes may be less suitable for bilingual children who are exposed to the target language less than monolingual peers. This study evaluates the concurrent and predictive value of a novel, computerized NWRT implemented in the MuLiMi web-platform and its potential in the discrimination of bilingual children with and without DLD, investigating the role of nonwords’ language specificity. Thirty-seven children (of whom 17 had an objective risk of phonological disorders) with at least one Italian-speaking parent, living and attending kindergartens in Germany were tested with the MuLiMi NWRT and German standardized language tests. Caregivers and kindergarten teachers filled in questionnaires. Fourteen of the children were re-tested after 8 to 12 months. The results suggest that the new test’s concurrent and discriminative validity are good. Analysis of variance revealed highly significant differences between children with and without (an objective risk of) phonological disorders and a significant interaction between nonword specificity and risk group. Significant correlations of initial scores with follow-up scores collected after 8-12 months were also found, as well as correlations with improvements in language abilities. In conclusion, although both language-specific and language-non-specific nonword repetition can support DLD risk identification in bilingual children, language-specific stimuli appear to be particularly sensitive indicators. This is interpreted as confirming DLD children’s reduced sensitivity to frequent, familiar characteristics of the linguistic stimuli. The test discriminative and concurrent validity showed to be robust to various potentially influencing factors like patterns of language exposure.